Effect of subthalamic nucleus deep brain stimulation on visual scanning. Issue 11 (November 2018) - Tokushige, Shin-ichi; Matsuda, Shun-ichi; Oyama, Genko; Shimo, Yasushi; Umemura, Atsushi; Sasaki, Takuya; Inomata-Terada, Satomi; Yugeta, Akihiro; Hamada, Masashi; Ugawa, Yoshikazu; Tsuji, Shoji; Hattori, Nobutaka; et al.
Highlights: We studied how deep brain stimulation (DBS) affects eye movements made during visual scanning. DBS increased the amplitude of voluntary saccades, but not reflexive saccades. DBS mainly affects voluntary saccades mediated by the basal ganglia. Abstract: Objective: Deep brain stimulation (DBS) can provide insights into the workings of the basal ganglia (BG) by interfering with their function. In patients with Parkinson's disease (PD) treated with DBS of the subthalamic nucleus, we studied the effect of DBS on scanning eye movements. Methods: In the visual memory task, subjects viewed images of various complexities for later recall. In visual search tasks, subjects looked for and fixated one odd target ring, embedded among 48 Landolt rings, which either stood out or not from the distractors. We compared the parameters of scanning saccades when DBS was on and off. Results: In the visual memory task, DBS increased the amplitude of saccades scanning simple but not complex drawings. In the visual search tasks, DBS showed no effect on saccade amplitude or frequency. Conclusions: Saccades when viewing simple images were affected by DBS since they are internally guided saccades, for which the involvement of BG is large. In contrast, saccades when viewing complex images or during visual search, made with the help of visual cues in the images (externally guided saccades) and less dependent on BG, were resistant to the effect of DBS. Significance: DBS affects saccades differentially depending on the task.